2004
DOI: 10.2105/ajph.94.7.1147
|View full text |Cite
|
Sign up to set email alerts
|

Medically Eligible Women Who Do Not Use HAART: The Importance of Abuse, Drug Use, and Race

Abstract: One of 4 women for whom HAART was indicated reported not using HAART. Childhood sexual abuse prevention, more intensive abuse treatment, and continuing drug treatment may enhance HIV disease treatment of women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
121
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(127 citation statements)
references
References 31 publications
5
121
1
Order By: Relevance
“…10 Both alcohol and drug abuse are associated with poor ART adherence and viral suppression failure. [10][11][12] Approximately 55% of women living with HIV/AIDS have experienced intimate partner violence (IPV). 13 A history of trauma, abuse, and violence for HIV-infected women is associated with decreased medication adherence, 9,11,12 and increased viral load.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Both alcohol and drug abuse are associated with poor ART adherence and viral suppression failure. [10][11][12] Approximately 55% of women living with HIV/AIDS have experienced intimate partner violence (IPV). 13 A history of trauma, abuse, and violence for HIV-infected women is associated with decreased medication adherence, 9,11,12 and increased viral load.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Approximately 55% of women living with HIV/AIDS have experienced intimate partner violence (IPV). 13 A history of trauma, abuse, and violence for HIV-infected women is associated with decreased medication adherence, 9,11,12 and increased viral load. 13,14 Studies consistently document high prevalence of mental health disorders and symptomatology among HIV positive populations.…”
Section: Introductionmentioning
confidence: 99%
“…6 In women with HIV, histories of abuse are quite prevalent, 8,9 and have been linked to risky sexual behaviors, HIV medication nonadherence, antiretroviral failure, and increased mortality. 2,3,8,[10][11][12][13] With highly active antiretroviral therapy (HAART), the HIV infection course has changed to that of a chronic illness. Moderate to high levels of adherence are necessary to achieve viral suppression (i.e., undetectable HIV viral load), reverse immune decline (e.g., improved CD4 + cell count), and decrease risk of morbidity and mortality.…”
mentioning
confidence: 99%
“…[22][23][24] Numerous barriers to HIV medication adherence and overall HIV access to care have been reported, including depression, stigma, disclosure, and drug/alcohol use. [25][26][27][28] A history of trauma or abuse among women with HIV has also been linked significantly to medication nonadherence, 3,11,29 as well as to antiretroviral failure and increased mortality. 2,3,8,11,13 Machtinger and colleagues 3 found that among HIV + biological and transgender women, those who reported recent trauma had over four-times the odds of antiretroviral failure in comparison to HIV + women who did not report recent trauma.…”
mentioning
confidence: 99%
See 1 more Smart Citation